Does the policy regarding the role of the national examination in determining graduation affect student achievement? - Rasmuin, Rasmuin (Jurnal Penelitian dan Evaluasi Pendidikan, 2022)
From 2004 to 2018, the national examination (NE) has undergone three policy changes regarding its role in determining graduation. The NE score was decided to be the sole determining factor for student graduation in the period 2004 to 2010, with the school examination score being the determinant of student graduation from 2011 to 2015 and no longer a determinant of student graduation from 2016 to 2018 period. This study aimed to analyze the pattern of influence of the NE policy as a determinant of graduation on student achievement at junior, senior, and vocational high schools. This study used data on student achievement for 15 years in the subjects tested on the NE obtained from the Research and Development Center of the Indonesian Ministry of National Education. Data analysis was done descriptively by estimating students' mean achievement on the NE and then analyzing the mean trend. By analyzing the trend of student scores' mean on the subjects tested on the NE at the junior high school, senior high school, and vocational high school levels, the mean tends to increase in the period 2004 to 2010, tends to be less stable and decrease in the period 2011 to 2015, and tends to decline again when the NE score is no longer used as a determinant of graduation in the period 2016 to 2018. These results indicate that the policy on using NE scores in determining graduation influences student achievement in junior high school, senior high school, and vocational high school levels.